Visitors’ motivation and willingness to pay for conservation in selected zoos in southwest Nigeria - B.O. Adetola; O.P. Adedire (Journal of Applied Sciences and Environmental Management, 2018)
The motivation and willingness to pay for ecotourism and wildlife conservation at the University of Ibadan and Obafemi Awolowo University Zoos in Southwest Nigeria were investigated. Structured Questionnaire was used to elicit information from two hundred and forty (240) visitor and data were analysed using descriptive and inferential (Chi-Square, Correlation) statistics. Findings from this study show that 50.4% of the visitors were female, 37.9% and 37.1% were within the age range of 15-24 years and 25-54 years respectively, 46.7% were married, and 43.3% attained to tertiary level of education. Furthermore, 66.2% of the visitors were employed with 39.6% earning ₦81, 000 (265.57 USD) and above as their monthly income. The main motivations of the zoo visitors are to see the condition of habitat and diversity of wildlife at the zoos, proximity to their residence and viewing wild animals. The starting bid for visitors to the zoos shows their willingness to pay for conservation services at the zoos. Income (r = 0.25, p = 0.00) had effect on the visitation pattern of the visitors. Relationship exists between the visitors’ motivation (r = 0.23, p = 0.00) and their level of satisfaction. The age (r = 0.15, p = 0.02), income (r = 0.13, p = 0.04), marital status (χ2 = 68.79, p = 0.01), religion (χ2 = 45.06, p = 0.04) of the visitors have impact on their willingness to pay for conservation at the zoos.